WEB PROFIL DAN SISTEM INFORMASI SEBAGAI MEDIA PROMOSI PADA CV.BAROKAH AGRO JAMBI: COMPANY PROFILE, PROMOTION, WEB, CUSTOMERS - Sany, Ezrifal (FORTECH (Journal of Information Technology), 2019)
Information spreads very quickly through various media and in various forms. Previously, the company promoted by displaying company profiles in the form of brochures, pamphlets and newspapers. But the weakness of all that itself is costly and takes time from production to distribution such as brochures to customers. The solution is to create a web-based company profile. company profile is an asset of an institution or company that can be used to enhance the company's image to establish cooperative relationships with companies and other related institutions. Research conducted at CV. Barokah Agro so consumers know what CV Barokah Agro is. The research method used is observation, interviews, analysis and implementation of web-based company profiles. And the company hopes that web-based profiles can be made more innovative and facilitate market reach.